Compost critters - Lavies, Bianca (Massachusetts : Silver Birdett Ginn, 1996)
Nature's recyclers receive a close-up look, in a study of the creatures from bacteria and fungo to worms and millipedse that break down our garbage returning raw materials to the earth.
Keywords: Compost; Ecology; Soils